Steam generators for nuclear power plants - Sadek, Sinisa; Hornacek, Martin, et.al. contributors (Unites States of America : Excelic Press, 2020)
Steam Generators for Nuclear Power Plants examines all phases of the lifecycle of nuclear steam generators (NSGs), components which are essential for the efficient and safe operation of light water reactors (LWRs). Coverage spans the design, manufacturing, operation and maintenance, fitness-for-service, and long-term operation of these key reactor parts. Part One opens with a chapter that provides fundamental background on NSG engineering and operational experiences. Following chapters review the different NSG concepts, describe NSG design and manufacturing, and consider the particularities of SGs for VVER reactors. Part Two focuses on NSG operation and maintenance, starting with an overview of the activities required to support reliable and safe operation. The discussion then moves on to tubing vibration, followed by the water and steam cycle chemistry issues relevant to the NSG lifecycle. Finally, a number of chapters focus on the key issue of corrosion in NSGs from different angles. This book serves as a timely resource for professionals involved in all phases of the NSG lifecycle, from design, manufacturing, operation and maintenance, to fitness-for-service and long-term operation. It is also intended as a valuable resource for students and researchers interested in a range of topics relating to NSG lifecycle management.
Part I: Design and Manufacturing 1. Introduction to nuclear steam generators 2. Nuclear steam generator design 3. Nuclear steam generator manufacturing 4.Thermal hydraulics, circulation and steam-water separation in nuclear steam generators 5. Design and operation of VVER steam generators Part II: Operation and Maintenance 6. Water and steam cycle chemistry relevant to nuclear steam generators 7. Corrosion Problems Affecting Steam Generator Tubes in Commercial Water Cooled Nuclear Power Plants 8. Environmental degradation of materials in nuclear steam generators 9. Corrosion product transport and fouling in nuclear steam generators 10. Corrosion hideout and hideout return in nuclear steam generators 11. Deposit management in nuclear steam generators: Chemical cleaning and decontamination 12. Thermal Performance Degradation 13. Tube vibration in nuclear steam generators 14. Structural integrity of nuclear steam generators 15. Nuclear steam generator inspection and testing 16. Nuclear steam generator tube inspection tools 17. Nuclear steam generator fitness-for-service assessment 18. Regulatory requirements and consideration for nuclear steam generators
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Nuclear power plants; Steam-boilers.; Nuclear power plants; Steam-boilers.